The first year of assisted dying in New Zealand through the lens of healthcare professionals not directly involved in the process - Waqas Arshad; Aida Dehkhoda; Melissa Carey; David B. Menkes; Nicholas Hoeh; Frederick Sundram; Rosemary Frey; Gary Cheung (BMC Palliative Care)
Abstract Background New Zealand’s End of Life Choice Act 2019 was enacted in 2021, allowing terminally ill people experiencing unbearable suffering to request assisted dying if they are expected to die within six months. Healthcare professionals not directly involved in assisted dying provision may have unique perspectives on implementation, yet this remains under-explored. Methods This qualitative study was conducted between June and November 2022. We used purposive and snowball sampling to recruit potential participants through various sources, including the Ministry of Health’s assisted dying training and communication email list. A multidisciplinary research team developed a semi-structured interview guide. The individual interviews were recorded, transcribed, and thematically analysed to identify core themes. Results Ten healthcare professionals with palliative and primary care backgrounds participated. Five main themes were generated: diverse views on assisted dying; views on the End of Life Choice Act; the interface between palliative care and assisted dying services; education on palliative care and assisted dying; and self-care coping and support. Participants expressed varied attitudes and ethical concerns, with most emphasising the need for reforms in eligibility criteria and improved public understanding. These healthcare professionals provided valuable insights into the broader impact of assisted dying on the healthcare system and the complexities of integrating it with palliative care. Conclusions Integration between palliative care and assisted dying services is crucial for delivering patient-centred care and addressing stigma surrounding end-of-life choices in New Zealand. Adapting international policies around eligibility criteria and safeguards can help streamline the process.